2008
DOI: 10.1111/j.1745-7254.2008.00901.x
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antitumoral activity and induction of apoptosis by novel pan Bcl-2 proteins inhibitor apogossypolone with adriamycin in human hepatocellular carcinoma

Abstract: Aim: To investigate the in vitro and in vivo activities and related mechanism of apogossypolone (ApoG2) alone or in combination with adriamycin (ADM) against human hepatocellular carcinoma (HCC). Methods: The IC 50 of ApoG2 in vitro was tested by WST assay, and the synergistic effect was analyzed using the CalcuSyn method. Cell apoptosis was determined using 4',6-diamidino-2-phenylindole staining and flow cytometric analysis. Western blotting was used to determine the expression of apoptosis-related proteins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…As one of the broad-spectrum anti-tumor drugs, doxorubicin (DOX) has been widely used for tumor combination therapy with other anti-tumor drugs [21,22]. Mi et al found that ApoG2 had a significant in vivo anti-tumor effect in combination with DOX and promoted the therapy effect of chemotherapy agent DOX in human hepatocellular carcinoma [23]. Therefore, combination therapy with ApoG2 and DOX is a potential method to improve the individual therapy effect of ApoG2 and DOX alone.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the broad-spectrum anti-tumor drugs, doxorubicin (DOX) has been widely used for tumor combination therapy with other anti-tumor drugs [21,22]. Mi et al found that ApoG2 had a significant in vivo anti-tumor effect in combination with DOX and promoted the therapy effect of chemotherapy agent DOX in human hepatocellular carcinoma [23]. Therefore, combination therapy with ApoG2 and DOX is a potential method to improve the individual therapy effect of ApoG2 and DOX alone.…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent improvements in surveillance programs and diagnostic tools allowing identification of small suspicious nodules, only 30% to 40% of patients with HCC are eligible for curative treatments [4] . In well-selected patients, resection and liver transplantation provide 5-year survival rates of 70%, whereas local ablation with radio frequency results in a 5-year survival rate of 50% [5] . These treatments change the natural course of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have greatly expanded the range of cancer cell lines sensitive to ApoG2. It was found to be active against hepatocellular cancer cell lines with IC 50 values ranging from 17 to 31 μM [124]. ApoG2 also enhanced the activity of adryamicin on these cell lines.…”
Section: Gossypolone/apog2mentioning
confidence: 93%